1999
DOI: 10.1074/jbc.274.36.25892
|View full text |Cite
|
Sign up to set email alerts
|

Fish Oil Feeding Decreases Mature Sterol Regulatory Element-binding Protein 1 (SREBP-1) by Down-regulation of SREBP-1c mRNA in Mouse Liver

Abstract: Dietary fish oil induces hepatic peroxisomal and microsomal fatty acid oxidation by peroxisome proliferator-activator receptor ␣ activation, whereas it downregulates lipogenic gene expression by unknown mechanism(s). Because sterol regulatory element-binding proteins (SREBPs) up-regulated lipogenic genes, investigation was made on the effects of fish oil feeding on SREBPs and sterol regulatory element (SRE)-dependent gene expression in C57BL/6J mice. Three forms of SREBPs, SREBP-1a, -1c, and -2, are expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
256
4
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 348 publications
(296 citation statements)
references
References 46 publications
30
256
4
3
Order By: Relevance
“…The mRNA level of SREBP-1c was not significantly influenced by lipid type or C. butyricum addition. This contradicts previous studies demonstrating that polyunsaturated fatty acids (PUFA) inhibited lipogenic gene transcription by suppressing SREBP-1c expression (Kim et al, 1999;Xu et al, 1999). Xu et al (1999) also indicated that the SREBP-1 mRNA content of cells was reduced by 20:4n-6 fatty acids in a dose-dependent manner, whereas 18:1n-9 had no effect.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…The mRNA level of SREBP-1c was not significantly influenced by lipid type or C. butyricum addition. This contradicts previous studies demonstrating that polyunsaturated fatty acids (PUFA) inhibited lipogenic gene transcription by suppressing SREBP-1c expression (Kim et al, 1999;Xu et al, 1999). Xu et al (1999) also indicated that the SREBP-1 mRNA content of cells was reduced by 20:4n-6 fatty acids in a dose-dependent manner, whereas 18:1n-9 had no effect.…”
Section: Discussioncontrasting
confidence: 74%
“…There have been numerous reports on how fish oil affects fatty acid metabolism in mammals (Ribeiro et al, 1991;Kim et al, 1999;Yu et al, 2010), but few have focused on birds. Moreover, the effects of dietary C. butyricum on the expression of genes linked to fatty acid metabolism have not been examined in chickens.…”
Section: Introductionmentioning
confidence: 99%
“…Diet preparations were similar to those of our previous studies. 5,6 Fish oil was provided by NOF Corp. (Tokyo, Japan). Butter was purchased from Snow Brand Milk Corp. (Hokkaido, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…4 This effect is attributable mainly to the combined effects of inhibition of lipogenesis and stimulation of fatty acid oxidation in the liver. 5,6 Fish oil supplementation may be effective in the prevention of NAFLD; however, it is not clear whether fish oil is effective against all types of fatty liver.…”
mentioning
confidence: 99%
“…∆9 desaturase is regulated at the molecular level by SREBP-1c [63]. Kim et al [64] demonstrated that fish oil downregulated ∆9 desaturase expression by inhibiting the synthesis of mRNA of SREBP-1c. Thus, the inhibition of ∆9 desaturase is with its inhibiting effect on lipogenesis and its stimulating effect on fatty acid oxidation another mechanism by which it decreases lipid synthesis and triglycerides in the liver.…”
Section: Patients With Nonalcoholic Steatohepatitismentioning
confidence: 99%